Drought regimens predict life history strategies in Heliophila. Issue 4 (23rd June 2019) - Monroe, J. Grey; Gill, Brian; Turner, Kathryn G.; McKay, John K.
Summary: Explaining variation in life history strategies is an enduring goal of evolutionary biology and ecology. Early theory predicted that for plants, annual and perennial life histories reflect adaptations to environments that experience alternative drought regimens. Nevertheless, empirical support for this hypothesis from comparative analyses remains lacking. Here, we test classic life history theory in Heliophila L. (Brassicaceae), a diverse genus of flowering plants native to Africa, controlling for phylogeny and integrating 34 yr of satellite‐based drought detection with 2192 herbaria occurrence records. We find that the common ancestor of these species was likely to be an annual, and that perenniality and annuality have repeatedly evolved, an estimated seven and five times, respectively. By comparing historical drought regimens, we show that annuals rather than perennial species occur in environments where droughts are significantly more frequent. We also find evidence that annual plants adapt to predictable drought regimens by escaping drought‐prone seasons as seeds. These results yield compelling support for longstanding theoretical predictions by revealing the importance of drought frequency and predictability to explain plant life history. More broadly, this work highlights scalable approaches, integrating herbaria records and remote sensing to address outstanding questions in evolutionary ecology.